2022
DOI: 10.3389/fimmu.2022.804987
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Effects of Sea Louse (Lepeophtheirus salmonis) Infection and Formalin-Killed Aeromonas salmonicida on Atlantic Salmon Skin Transcriptome

Abstract: Lepeophtheirus salmonis (sea lice) and bacterial co-infection threatens wild and farmed Atlantic salmon performance and welfare. In the present study, pre-adult L. salmonis-infected and non-infected salmon were intraperitoneally injected with either formalin-killed Aeromonas salmonicida bacterin (ASAL) or phosphate-buffered saline (PBS). Dorsal skin samples from each injection/infection group (PBS/no lice, PBS/lice, ASAL/no lice, and ASAL/lice) were collected at 24 h post-injection and used for transcriptome p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 168 publications
0
3
0
Order By: Relevance
“…The study found that the up-regulated genes were associated with glycolysis, the interferon pathway, complement cascade activity, and heat shock protein family, while the down-regulated genes were related to antigen presentation and processing, T-cell activation, collagen formation, and extracellular matrix ( 15 ). Co-infection of sea lice ( Lepeophtheirus salmonis ) with formalin-killed Aeromonas salmonicida activated the pathways involved in the innate (e.g., neutrophil degranulation) and adaptive immunity (e.g., antibody formation), and endothelial cell migration ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the up-regulated genes were associated with glycolysis, the interferon pathway, complement cascade activity, and heat shock protein family, while the down-regulated genes were related to antigen presentation and processing, T-cell activation, collagen formation, and extracellular matrix ( 15 ). Co-infection of sea lice ( Lepeophtheirus salmonis ) with formalin-killed Aeromonas salmonicida activated the pathways involved in the innate (e.g., neutrophil degranulation) and adaptive immunity (e.g., antibody formation), and endothelial cell migration ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the susceptibility of Atlantic salmon to both sea louse species, restoring Atlantic salmon’s adaptive nutritional immunity may not be sufficient to confer resistance to L. salmonis . However, this may still result in positive animal welfare consequences given that iron limitation can prevent opportunistic microbial infections [166] that are often associated with the sites of sea lice attachment [167].…”
Section: Discussionmentioning
confidence: 99%
“…SAAs are known APPs in rainbow trout ( Oncorhynchus mykiss ), Atlantic salmon ( Salmo salar ), and other teleosts [ 9 , 10 , 11 , 12 ] making these proteins attractive markers by which to monitor fish health status. Atlantic salmon SAA-5 transcripts were reported as the dominant APP response following Aeromonas salmonicida challenge [ 13 ].…”
Section: Introductionmentioning
confidence: 99%